2021
DOI: 10.1007/s13193-021-01478-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Cancer Surgical Services—AIIMS, New Delhi Experience

Abstract: COVID pandemic has impacted cancer care delivery and cancer surgical services globally. There is an urgent need to study the extent of the impact of COVID on cancer surgery and individual institutional response and strategies adopted to counter the adverse impact. A review of administrative and clinical policy changes adopted at the tertiary cancer center to combat COVID pandemic and resume cancer surgical services were performed. A retrospective comparative analysis of cancer out-patient census during COVID p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…Our results confirmed the impact of COVID-19 pandemic, especially during the early waves, similar to what has been documented in other countries. 3,4 In particular, the reduction we found was lower than the decrease of −33.9% (95% CI: −39.9; −27.9) in cancer surgical treatments administered during the pandemic globally, while it was more consistent with the reduction reported in Europe, that is, −20.9% (95% CI: −30.1; −11.7). 19 This heterogeneity is not limited to cross-country comparisons but it has been reported also within Italy, especially when considering surgeries for different cancer sites.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our results confirmed the impact of COVID-19 pandemic, especially during the early waves, similar to what has been documented in other countries. 3,4 In particular, the reduction we found was lower than the decrease of −33.9% (95% CI: −39.9; −27.9) in cancer surgical treatments administered during the pandemic globally, while it was more consistent with the reduction reported in Europe, that is, −20.9% (95% CI: −30.1; −11.7). 19 This heterogeneity is not limited to cross-country comparisons but it has been reported also within Italy, especially when considering surgeries for different cancer sites.…”
Section: Discussioncontrasting
confidence: 60%
“…Worldwide, governments implemented containment policies and restrictive measures to limit the spread of the virus, impacting the general population 2 . The indirect effects of the COVID‐19 pandemic on cancer care and surgical services have been widely acknowledged, revealing a decrease in hospitalization volumes worldwide, 3–5 both for emergency and nonemergency access 6 . The surge in COVID‐19 cases has created a critical demand for intensive care, straining hospital resources and staff.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Yanaral and Öz reported that in the pandemic period, the number of patients undergoing emergency and elective surgery decreased compared to the pre-pandemic period. [ 11 ] Furthermore, Schöni et al, reported that surgical interventions decreased during the pandemic period. [ 12 ] Unlike the literature, in our study, the number of post-operative patients admitted to ICU was higher during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] In India, in one hospital system in New Delhi, there was a 33.7% reduction in major cancer surgeries in 2020. 33 Unlike some other diseases, delays in cancer screening can lead to advanced disease at presentation, which can necessitate more complex surgical procedures that are associated with poor outcomes. The NCI predicted an additional 10,000 excess deaths over the next 10 years for breast and colorectal cancer patients due to delays in access to care during the COVID-19 pandemic.…”
Section: Impact Of the Covid-19 Pandemic And Delays In Cancer Surgica...mentioning
confidence: 99%
“…There were reductions in the number of cancer surgeries, delays in radiotherapy and chemotherapy, as well as reductions in supply chains that were crucial for surgical equipment 29–32 . In India, in one hospital system in New Delhi, there was a 33.7% reduction in major cancer surgeries in 2020 33 …”
Section: Introductionmentioning
confidence: 99%